2021
DOI: 10.20944/preprints202107.0190.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Natural Degradant of Curcumin, Feruloylacetone Inhibits Cell Proliferation via Inducing Cell Cycle Arrest and a Mitochondrial Apoptotic Pathway in HCT116 Colon Cancer Cells

Abstract: Feruloylacetone (FER) is a natural degradant of curcumin after heating, which structurally reserves some functional groups of curcumin. It is not as widely discussed as its original counterpart in previous studies and, therefore, its anti-cancer efficacy is investigated herein. This study focuses on the suppressive effect of FER on colon cancer, as the efficacious effect of curcumin on this typical cancer type has been well evidenced. In addition, demethoxy-feruloylacetone (DFER) was applied to compare the eff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Also, Yadav et al demonstrated identical cyclin-CDK downregulation in pancreatic cancer cells under the influence of ciprofloxacin, moxifloxacin and gatifloxacin driven cell cycle arrest in two separate experiments. In one of their investigations, it was discovered that gatifloxacin caused to G2phase arrest in pancreatic cancer cells through the p53 pathway (11,20). This investigation of great significance as it hypothesizes that gatifloxacin stabilizes mutant-p53 and return its wild type role in these cells.…”
Section: Inducing Cell Cycle Arrest By Fqsmentioning
confidence: 99%
“…Also, Yadav et al demonstrated identical cyclin-CDK downregulation in pancreatic cancer cells under the influence of ciprofloxacin, moxifloxacin and gatifloxacin driven cell cycle arrest in two separate experiments. In one of their investigations, it was discovered that gatifloxacin caused to G2phase arrest in pancreatic cancer cells through the p53 pathway (11,20). This investigation of great significance as it hypothesizes that gatifloxacin stabilizes mutant-p53 and return its wild type role in these cells.…”
Section: Inducing Cell Cycle Arrest By Fqsmentioning
confidence: 99%
“…Curcumin is one of the most prominent bioactive natural phytochemicals known as the polyphenols found in turmeric, 100 even though it is limited by poor oral bioavailability. 101 It has been previously reviewed that curcumin could only be detected in extremely low concentration in blood and extraintestinal tissue, and it could hardly be absorbed, was rapidly metabolized and chemically unstable, and would be eliminated rapidly in the system. 102 However, due to its compelling performance in several disease preventions, increasing studies focused on improving the bioavailability of curcumin through encapsulation strategies.…”
Section: Phytochemicals Impair Mitochondria To Achieve Cancer Preventionmentioning
confidence: 99%